Easy recovery through environment awareness - Hassan, Sa'adah (2008)
Recovery is the action of getting back or regaining to former status. This action involves in obtaining usable resources that are available. Thus, having awareness of the computing system's operating environment is useful either as to identify factor that can affect the system or to seek out alternative resources available in the environment. This paper presents the implementation of environment awareness in computing systems, with emphasis on facilitating user recovery from service failure by taking benefit of information from the environment where the systems operate. the discussion is illustrated with prototype developed.